Research Support Priorities of and Relationships among Librarians and Research Administrators: A Content Analysis of the Professional Literature - Bradley, Cara (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2018)
Objective - This research studied the recent literature of two professions, library and information studies (LIS) and research administration (RA), to map the priorities and concerns of each with regard to research support. Specifically, the research sought to answer these research questions: (1) What are the similarities and differences emerging from the LIS and RA literatures on research support? (2) How do librarians and research administrators understand and engage with each other’s activities through their professional literatures? (3) Do Whitchurch’s (2008a, 2008b, 2015) concepts of bounded-cross-boundary-unbounded professionals and theory of the “third space” provide a useful framework for understanding research support?Methods - The research method was a content analysis of journal articles on research-related topics published in select journals in the LIS (n = 195) and RA (n = 95) fields from 2012-2017. The titles and abstracts of articles to be included were reviewed to guide the creation of thematic coding categories. The coded articles were then analyzed to characterize and compare the topics and concerns addressed by the literature of each profession.Results - Only two (2.2%) RA articles referred to librarians and libraries in their exploration of research support topics, while six (3.1%) LIS articles referred to the research office or research administrators in a meaningful way. Of these six, two focused on undergraduate research programs, two on research data management, and two on scholarly communications. Thematic coding revealed five broad topics that appeared repeatedly in both bodies of literature: research funding, research impact, research methodologies, research infrastructure, and use of research. However, within these broad categories, the focus varied widely between the professions. There were also several topics that received considerable attention in the literature of one field without a major presence in that of the other, including research collaboration in the RA literature, and institutional repositories, research data management, citation analysis or bibliometrics, scholarly communication, and open access in the LIS literature.Conclusion - This content analysis of the LIS and RA literature provided insight into the priorities and concerns of each profession with respect to research support. It found that, even in instances where the professions engaged on the same broad topics, they largely focused on different aspects of issues. The literature of each profession demonstrated little awareness of the activities and concerns of the other. In Whitchurch’s (2008a) taxonomy, librarians and research administrators are largely working as “bounded” professionals, with occasional forays into “cross-boundary” activities (p. 377). There is not yet evidence of “unbounded” professionalism or a move to a “third space” of research support activity involving these professions (Whitchurch, 2015, p. 85). Librarians and research administrators will benefit from a better understanding of the current research support landscape and new modes of working, like the third space, that could prove transformative.